Flexible Electrodes for Brain–Computer Interface System - Wang, Junjie; Wang, Tengjiao; Liu, Haoyan; Wang, Kun; Moses, Kumi; Feng, Zhuoya; Li, Peng; Huang, Wei (Advanced materials (Weinheim), 2023)
Brain–computer interface (BCI) has been the subject of extensive research recently. Governments and companies have substantially invested in relevant research and applications. The restoration of communication and motor function, the treatment of psychological disorders, gaming, and other daily and therapeutic applications all benefit from BCI. The electrodes hold the key to the essential, fundamental BCI precondition of electrical brain activity detection and delivery. However, the traditional rigid electrodes are limited due to their mismatch in Young's modulus, potential damages to the human body, and a decline in signal quality with time. These factors make the development of flexible electrodes vital and urgent. Flexible electrodes made of soft materials have grown in popularity in recent years as an alternative to conventional rigid electrodes because they offer greater conformance, the potential for higher signal‐to‐noise ratio (SNR) signals, and a wider range of applications. Therefore, the latest classifications and future developmental directions of fabricating these flexible electrodes are explored in this paper to further encourage the speedy advent of flexible electrodes for BCI. In summary, the perspectives and future outlook for this developing discipline are provided. The brain projects around the world, the classification of electrical neural signals, the applications of brain–computer interface, drawbacks of rigid electrodes, and the necessity to switch to flexible electrodes, are briefly introduced in this article. Then the classification of different type of electrodes, electrode materials, fabrication methods, flexible substrates, and extra requirements for flexible electrodes have been systematically reviewed.